Mystical Theology Redux: The Pattern of Aquinas’Summa Theologiae - Williams, A. N. (Modern theology, 1997)
The deleterious effects of the modern divorce of spirituality and theology can and must be redressed by the revival of mystical theology, theology that is ultimately concerned with the union of God and humanity. Aquinas’Summa Theologiae provides a model of such a mystical theology, a work which is both an exhortation to contemplation and an act of contemplation. The mystical themes of the Summa are evident in four operative principles, the theoretical, the theological, the anthropological and the Christological, which bind the work together and specify the way in which Thomas articulates the union of God and humanity.